Examining Risk for Sexual Assault Among Bisexuals - Ménard, Kim S. (Crime & delinquency, 2025)
The current study examines rates of victimization by sexual orientation disaggregated by sex (female = 7,972; male = 6,985) using the National Longitudinal Study of Adolescent to Adult Health data (wave IV). Results from design-adjusted logistic regression analyses indicate bisexual people, regardless of sex, are most at risk for forced sexual assault. While women, especially bisexual women, had higher rates of sexual victimization, differences in risk were larger for bisexual men versus straight men than for bisexual women versus straight women. Bisexual respondents were likely to engage in alcohol-related risky behaviors, lifestyle factors did not fully account for differences in victimization risk among bisexuals. Results highlight the need for awareness, prevention, and intervention policies, particularly with regard to bisexual identities.